Experiences and Interventions by Botswana police officers in providing emergency care in road traffic collisions in the greater Gaborone region - M. Sebakeng; M. Cox (African Journal of Emergency Medicine, 2023)
Background: Close to 500 people die annually from Road Traffic Collisions in Botswana. The country's Emergency Medical Service is limited in capacity and coverage and greatest in the region of the capital city, Gaborone. Botswana Police Service officers are often first responders to the incidents and provide first aid, however the extent of their interventions and their experiences has not been studied. Methods: A questionnaire based cross-sectional survey was conducted in January 2016 on a sample of 99 officers on past pre-hospital care training, attitudes towards providing pre-hospital care for accident victims, the number of road traffic collision related deaths and injuries encountered in the last 6 months, their interventions to the victims and limitations encountered in providing care. Results: The officers self-reported attending to a median of 10 injured victims (IQR = 5 – 20) and a median of 2 deaths (IQR = 0 – 4) in the preceding 6 months. The officers generally acknowledged their role and responsibility to provide pre-hospital care to the victims. Officers frequently secured accident scenes and transported injured victims to health facilities. They rarely performed haemorrhage control on victims, performed any airway manoeuvres or splint injured limbs. The major limitations to providing care were lack of first aid supplies and personal protective equipment, lack of knowledge and skills to provide care and interference from onlookers at accident scenes. Conclusion: Botswana Police officers in the greater Gaborone area attend to a considerable number of traffic related injuries and fatalities. These results support many opportunities for educational interventions to add value to pre-hospital care.